Orientational ordering in monolayers of ortho–para hydrogen: Physics in Quantum Crystals - Kokshenev, V.B.; Sullivan, N.S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
We discuss orientational ordering in monolayers of solid hydrogen in view of recent experimental findings in NMR studies of (ortho)c–(para)1–c-hydrogen mixtures on boron nitride substrate. Analysis of the temperature-concentration behavior for the observed NMR frequency splitting is given on the basis of a two-dimensional (J = 1)c–(J = 0)1–c-rotor model with the quadrupolar coupling constant Г0 = (0.50 ± 0.03) K and the crystalline field amplitude V0 = (0.70 ± 0.10) K derived from experiment. The two distinct para-rotational short-range ordered structures are described in terms of the local alignment and orientation of the polar principal axis, and are shown to be due to the interplay between the positive and negative crystalline fields. It is shown that the local structures observed below the 2D site-percolation threshold cp = 0.72 are rather different from the ferromagnetic-type para-rotational ordering suggested earlier by Harris and Berlinsky.